2018
DOI: 10.1039/c8ra06692b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of annealing temperature on properties of InSnZnO thin film transistors prepared by Co-sputtering

Abstract: Indium-tin-zinc-oxide (ITZO) as the channel layer grown by co-sputtering of ZnO target and ITO target in the bottom gate thin-film transistors (TFTs) is proposed in this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…The O2 peak centered at ~531.2 eV corresponds to oxygen deficiencies in the lattices, such as VO. The O3 peak centered at ~532.3 eV is attributed to chemisorbed oxygen, such as adsorbed O2, H2O, and the bonded oxygen in -OH groups [21,22]. It is shown that the relative area of the O2 peak is reduced from 27.5% to 14.0% after Al2O3 passivation.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The O2 peak centered at ~531.2 eV corresponds to oxygen deficiencies in the lattices, such as VO. The O3 peak centered at ~532.3 eV is attributed to chemisorbed oxygen, such as adsorbed O2, H2O, and the bonded oxygen in -OH groups [21,22]. It is shown that the relative area of the O2 peak is reduced from 27.5% to 14.0% after Al2O3 passivation.…”
Section: Resultsmentioning
confidence: 97%
“…3 (a)-(c), the XPS spectra of the O 1s peak can be divided into three peaks: O1, O2, and O3, and further fitted by the Gaussian-Lorentzian. The O1 peak centered at ~530.4 eV corresponds to the oxygen bonded in the lattices, such as Zn-O, In-O, and Sn-O [21,22]. The O2 peak centered at ~531.2 eV corresponds to oxygen deficiencies in the lattices, such as VO.…”
Section: Resultsmentioning
confidence: 99%
“…The O 1 sub-peak (529.24 eV) is attributed to the oxygen-bonded metal in lattice, and the O 2 sub-peak (530.09 eV) is attributed to the oxygen-deficient regions related to oxygen vacancies. The O 3 sub-peak (531.13 eV) results from the chemisorbed oxygen related to the formation of metal hydroxide [42][43][44][45][46]. Figure 6b shows the relative area ratio of O 1 , O 2 , and O 3 peaks obtained from the ITO:Zn thin films with varied zinc content.…”
Section: Resultsmentioning
confidence: 99%
“…For the as-deposited ITZO thin film, the composition of peak 1: peak 2: peak 3 is 67.57%: 26.60%: 5.83% (Figure S4, Supporting Information), which is comparable to the reported data. [52][53][54][55][56] For the untreated ITZO thin film (25 °C), the composition of peak 1: peak 2: peak 3 become 45.51%: 30.25%: 24.24%, as shown in Figure 3a. The relative MV O concentration is slightly increased, compared with the as-deposited ITZO thin film.…”
Section: Mechanism Discussionmentioning
confidence: 99%